Advances in Induced Pluripotent Stem Cell-Derived Natural Killer Cell Therapy - Wenhua Qiao; Peng Dong; Hui Chen; Jianmin Zhang (Cells)
Natural killer (NK) cells are cytotoxic lymphocytes of the innate immune system capable of killing virus-infected cells and/or cancer cells. The commonly used NK cells for therapeutic applications include primary NK cells and immortalized NK cell lines. However, primary NK cell therapy faces limitations due to its restricted proliferation capacity and challenges in stable storage. Meanwhile, the immortalized NK-92 cell line requires irradiation prior to infusion, which reduces its cytotoxic activity, providing a ready-made alternative and overcoming these bottlenecks. Recent improvements in differentiation protocols for iPSC-derived NK cells have facilitated the clinical production of iPSC-NK cells. Moreover, iPSC-NK cells can be genetically modified to enhance tumor targeting and improve the expansion and persistence of iPSC-NK cells, thereby achieving more robust antitumor efficacy. This paper focuses on the differentiation-protocols efforts of iPSC-derived NK cells and the latest progress in iPSC-NK cell therapy. Additionally, we discuss the current challenges faced by iPSC-NK cells and provide an outlook on future applications and developments.